Stroke Recurrence in a Patient Twelve Years after Repair of a Secundum Atrial Septal Defect - Ok, Taedong; La, Yun Kyung; Cha, Hyun Seo; Cheon, Kyeongyeol; Choi, Bo Kyu; Yi, Gi Jong; Lee, Kyung-Yul (Journal of neurocritical care, 2018)
Background Secundum atrial septal defect (ASD) is a common congenital heart defect in adults. Patients with ASDs at high risk of cardiovascular complications undergo either surgical repair or percutaneous device closure. Case Report We report the case of an 85-year-old male with unusual recurrent cerebral infarctions. The patient has undergone repair of secundum ASD 12 years ago. Evaluation by transesophageal echocardiography revealed a mobile mass at the patch repair site in the left atrium. The mass was surgically removed due to recurrent stroke during the anticoagulation. Conclusion This case emphasizes the importance of regular cardiac checkup and the need to consider cardioembolic source as being part of the etiology of stroke recurrence, even if the event occurs many years after intracardiac shunt closures.